Structure-function studies of the alpha pheromone receptor from yeast - Robles, Laura Marina; Millán-Pacheco, César; Pastor, Nina; Del Río, Gabriel (TIP Revista Especializada en Ciencias Químico-Biológicas, 2016)
Ste2p is a G protein-coupled receptor (GPCR) in Saccharomyces cerevisiae that mediates mating by responding to the alpha-mating factor pheromone. Ste2p belongs to a subfamily of GPCRs with no global sequence similarity to GPCRs of known atomic three-dimensional structure, yet it shares functional similarities with many of these. To deepen our understanding of the structure-function relationship of this receptor, we built an atomic three-dimensional homology-based model of Ste2p that was used to simulate the docking of the alpha pheromone. The Ste2p model is in general agreement with the available experimental data and allowed us to propose that the interface between Ste2p and alpha pheromone is formed by 26 residues, most of which are polar residues located at the three extracellular loops and helices HI, H5, and H6. This interface does not include Ile190, a highly conserved residue among fungal species, located at the second extracellular loop and therefore a potential binding site residue. By performing mutagenesis of STE2 at this position we observed only a small effect of this residue in receptor signaling. Hence, the Ste2p model presented here is consistent in general with current experimental data and constitutes a framework to test hypothesis about the structure-function relationship of this receptor.